Expanding the Criminalization of Acts of Corruption According to the Law on the Prevention and Combating of Corruption - Dakhane, Amel (Journal of Legal Studies and Researches, 2021)
This study aims at identifying new forms of corruption that have been criminalized by the law 06-01 of prevention and fight against corruption, it seeks also to know to what extent the Algerian legislator is affected by the provisions of the International Convention concerning the legislative framework to criminalize these acts. This law concerns two types of corruption crimes: Traditional crimes previously organized in Penal Code, as well as new other crimes.